2001
DOI: 10.1046/j.1464-410x.2001.00102.x
|View full text |Cite
|
Sign up to set email alerts
|

Tumour angiogenesis and Ki‐67 expression in phaeochromocytoma

Abstract: Objective To determine the expression of CD34 (to evaluate vascularity) and Ki-67 (as a proliferative index) in a variety of phaeochromocytomas and thus assess the utility of these markers as possible predictors of malignancy. Patients and methods Deparaf®nized tissue sections from 21 patients with benign and four with malignant phaeochromocytoma were assessed immunohistochemically to evaluate microvascular counts (using CD34 antigen) and the proliferative index (Ki-67 antigen, monoclonal antibody MIB-1).Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 24 publications
3
21
0
Order By: Relevance
“…Although previous reports showed an increased proliferative activity in the central areas compared with the periphery of PTA (46), we found an even distribution of the vascular net through the entire gland. In addition, several studies performed in different endocrine tumors showed a lack of relationship between cell proliferation and angiogenesis (47)(48)(49). We did not find differences in the even distribution of blood vessels between different histological groups; thus, heterogeneity in vascularization between different regions of the gland is not likely to affect the results.…”
Section: Discussionmentioning
confidence: 41%
See 1 more Smart Citation
“…Although previous reports showed an increased proliferative activity in the central areas compared with the periphery of PTA (46), we found an even distribution of the vascular net through the entire gland. In addition, several studies performed in different endocrine tumors showed a lack of relationship between cell proliferation and angiogenesis (47)(48)(49). We did not find differences in the even distribution of blood vessels between different histological groups; thus, heterogeneity in vascularization between different regions of the gland is not likely to affect the results.…”
Section: Discussionmentioning
confidence: 41%
“…Another limitation of this study is that most of the so-called normal PTG are from patients with pHPT and are not strictly normal, because they are likely to be suppressed with respect to both secretory and proliferative activity compared with normal glands (46). However, we showed no relationship between vascularization and biochemical activity, and several studies in different endocrine tumors showed a lack of relationship between cell proliferation and angiogenesis (47)(48)(49); thus, we do not think the suppression of these normal glands influences the MVD. It is possible to hypothesize that angiogenesis, as in many other human cancers, plays a role in the progression of parathyroid carcinomas and that MVD and/or angiogenic growth factors could be used as a prognostic marker, or even further, as a potential therapeutic target.…”
Section: Discussionmentioning
confidence: 70%
“…The proliferation activity of tumour cells is a useful marker for estimating the growth potential in many tumours. Some authors have found a positive correlation between Ki-67 score (proliferation activity of the tumour) and malignant behaviour in pheochromocytomas [9,24,25,26]. However, the Ki-67 score is not a perfect tool: the score in most pheochromocytomas is low, between 0 and 2% [10,22,26].…”
Section: Discussionmentioning
confidence: 99%
“…Feng [14], Zielke [15] and Roojens [25] have observed a significantly greater number of blood vessels in metastasizing tumors. However, other authors did not confirm these results [13,26,27].…”
Section: Resultsmentioning
confidence: 83%